THE INCREASE OF MICROBIOLOGICAL ACTIVITY OF ACIDIC SOIL BY MEANS OF INOCULATION AND LIMING - Стаменов, Драгана; Јарак, Мирјана; Ђурић, Симонида; Хајнал-Јафари, Тимеа (Economics of Agriculture, 2011)
The aim of the investigation was to determine the fertility of acidic soil (pH 5.4) according to the number of microorganisms and their enzymatic activity, as well as to enhance productive properties of this soil using microbial inoculants and calcium carbonate. One half of soil samples were untreated and the investigation focused on examining the number of systematic and physiological groups of microorganisms, dehydrogenase, protease and urease activity. In the other half of samples calcium carbonate (5t/ha) and microbial inoculants were added. The soil was sown with red clover and the number of microorganisms, the length and the dry matter mass were determined 20 and 40 days later. The untreated soil samples were poor in the investigated groups of microorganisms whereas azotobacter was not registered at all. Enzymatic activity was low. As for the soil samples which were treated with calcium carbonate and microbial inoculants, an increase in the total number of bacteria, number of actinomycetes and azotobacter was observed. The greatest length and the dry matter mass of the plant were observed in the variants with rhizobia inoculation, with and without liming.